2008
DOI: 10.1002/ajmg.b.30756
|View full text |Cite
|
Sign up to set email alerts
|

Twin study refining psychotic symptom dimensions as phenotypes for genetic research

Abstract: We investigated which psychotic symptom dimensions are likely to be most useful as phenotypes for genetic linkage and association studies. Two hundred twenty-four probandwise twin pairs (106 monozygotic,118 same-sex dizygotic), where probands had psychosis, were ascertained from the Maudsley Twin Register in London. Dimensions were defined as ordinal symptom scores using the OPCRIT checklist, based on previous factor analyses of this and other samples. To qualify as a potentially useful phenotype, dimensions h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…However, the point estimate of 0.34 was similar to that found in affected sib-pairs using the same symptom dimension definition (Spearman r ¼ 0.25) [Cardno et al, 1999a] and closer still using the same statistical approach (PCC ¼ 0.30, CI 0.07-0.51: calculated by AG Cardno), and also similar using other rating scales, analytical approaches and samples (0.19-0.32) [Burke et al, 1996;Loftus et al, 1998;Cardno et al, 1999a;Rietkerk et al, 2008]. The sib-pairs had a narrower range of phenotypes-schizophrenia and schizoaffective disorder-but in this twin sample correlations for the disorganized dimension are similar in MZ pairs concordant for psychotic disorder, and where one or both twins has schizophrenia [Cardno et al, 2008] (there are too few DZ twin pairs concordant for schizophrenia for this comparison). Caveats are the nonsystematic ascertainment of the sib-pair samples and the theoretical possibility of differences in familial aggregation between DZ twins and siblings.…”
Section: Symptom Dimensionsmentioning
confidence: 53%
See 4 more Smart Citations
“…However, the point estimate of 0.34 was similar to that found in affected sib-pairs using the same symptom dimension definition (Spearman r ¼ 0.25) [Cardno et al, 1999a] and closer still using the same statistical approach (PCC ¼ 0.30, CI 0.07-0.51: calculated by AG Cardno), and also similar using other rating scales, analytical approaches and samples (0.19-0.32) [Burke et al, 1996;Loftus et al, 1998;Cardno et al, 1999a;Rietkerk et al, 2008]. The sib-pairs had a narrower range of phenotypes-schizophrenia and schizoaffective disorder-but in this twin sample correlations for the disorganized dimension are similar in MZ pairs concordant for psychotic disorder, and where one or both twins has schizophrenia [Cardno et al, 2008] (there are too few DZ twin pairs concordant for schizophrenia for this comparison). Caveats are the nonsystematic ascertainment of the sib-pair samples and the theoretical possibility of differences in familial aggregation between DZ twins and siblings.…”
Section: Symptom Dimensionsmentioning
confidence: 53%
“…Initial analysis of the Maudsley twin series [Cardno et al, 2001[Cardno et al, , 2008 showed similar correlations for positive dimension definitions in affected monozygotic (MZ) twin pairs (up Neuropsychiatric Genetics to 0.35), but trends towards higher correlations for some definitions of the negative and disorganized dimensions (up to 0.77). This suggests that there may be notable genetic influences on at least some dimensions, but these analyses did not include formal heritability estimates (see Supplementary Material).…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations